Morphological, Microstructure, Tensile and Water-Sorption Characteristics of Surface Modified Kenaf Fibre for Sustainable Biocomposite Reinforcement. Issue 13 (1st December 2022) - Ogunbode, Babatunde E.; Nyakuma, Bemgba B.; Lawal, Temitope A.; Yatim, Jamaludin M.; Abdul, Aliyu; Ayoosu, Moses I.
ABSTRACT: – The sustainable utilisation of Kenaf fibres (KF) as environmentally friendly reinforcement in mortar, concrete and polymer composites promotes the concept of a circular economy and sustainable construction. However, the hydrophilic nature of such biofibres adversely affects their structural applications as reinforcement in concrete, mortar and polymer. Therefore, the study examined the effect of alkali treatment (mercerization) on the surface sorption characteristics of KF. The effect of water sorption characteristics on the mechanical properties of surface-modified and untreated KF was also investigated in the study. Scanning electron microscopy was performed to examine the morphology and microstructure of the fibre surface along with the tensile fracture of the swollen/un-swollen fibres. The water absorption studies revealed that mercerization reduced the overall water uptake of KF by 16%, which enhanced the adhesion of the fibre surface. The findings provide the knowledge required by scientists and engineers for determining the water requirements for the design of bio-fibrous concrete composites.